Population Genomics of an Obligately Halophilic Basidiomycete Wallemia ichthyophaga - Gostinčar, Cene; Sun, Xiaohuan; Zajc, Janja; Fang, Chao; Hou, Yong; Luo, Yonglun; Gunde-Cimerman, Nina; Song, Zewei (Frontiers in Microbiology, 2019)
Background. Wallemia ichthyophaga is a highly specialised basidiomycetous fungus. It is one of the most halophilic fungi ever described, only able to grow at low water activity. This specialisation is thought to explain why it is only rarely isolated from nature. Results. Genomes of 21 W. ichthyophaga strains were sequenced with PE150 reads on BGISEQ500 platform. The genomes shared high similarity with the reference genome of the species, they were all smaller than 10 Mbp and had a low number of predicted genes. Groups of strains isolated in the same location encompassed clones as well as very divergent strains. There was little concordance between phylogenies of predicted genes. Linkage disequilibrium of pairs of polymorphic loci decayed relatively quickly as a function of distance between the loci (LD decay distance 1270 bp). For the first time a putative mating-type locus was identified in the genomes of W. ichthyophaga. Conclusions. Based on the comparison of W. ichthyophaga genomes it appears that some phylogenetic lineages of the species can persist in the same location over at least several years. Apart from this, the differences between the strains do not reflect the isolation habitat or geographic location. Together with results supporting the existence of (sexual) recombination in W. ichthyophaga, the presented results indicate that strains of W. ichthyophaga can form a single recombining population even between different habitats and over large geographical distances.